Maintaining an Influence: The Sisters of Saint Martha, Charlottetown, Respond to Social and Religious Change, 1965-85 - MacDonald, Heidi (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
Between 1965 and 1985, the Sisters of Saint Martha of Prince Edward Island used the expanding social welfare state to their advantage, successfully negotiating space within new secular social services structures and influencing government policy on the delivery of key social and health care services.